The Interrelationship between Periodontal Disease and Joint Disease (Rheumatoid Arthritis): A literature review (Research, Society and Development, 2024)
The objective of this article is to establish that periodontal diseases and rheumatoid arthritis have many parameters of similarity, especially with regard to the infection that both submit the patient to and with microbiological similarity, with the pathogen Porphiromonas gingivalis as a common infectant. Therefore, both rheumatology and periodontics have worked together to increase clinical studies so that the patient can be treated with the same multifactorial in order to influence a possible potentiation between diseases. We conclude that our organism has a interrelation between all the parts, and its not different between Bucal Disease and Rheumatoid Arthritis.